2017
DOI: 10.1073/pnas.1615484114
|View full text |Cite
|
Sign up to set email alerts
|

Lys49 myotoxin from the Brazilian lancehead pit viper elicits pain through regulated ATP release

Abstract: Pain-producing animal venoms contain evolutionarily honed toxins that can be exploited to study and manipulate somatosensory and nociceptive signaling pathways. From a functional screen, we have identified a secreted phospholipase A2 (sPLA2)-like protein, BomoTx, from the Brazilian lancehead pit viper (Bothrops moojeni). BomoTx is closely related to a group of Lys49 myotoxins that have been shown to promote ATP release from myotubes through an unknown mechanism. Here we show that BomoTx excites a cohort of sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 39 publications
2
32
1
Order By: Relevance
“…This suggests that PLA2s contribute to an increase in arachidonic acid release from cell membranes and its availability to be processed by cyclooxygenase resulting in prostaglandin production (Verri et al, 2006). Corroborating this hypothesis, studies performed in rodents have demonstrated that PLA2s isolated from different snake venoms induced hyperalgesia mediated by biogenic amines, cytokines, prostaglandins, sympathomimetic amines, ATP, K + release, purinergic receptor activation, and glial cell activation (Nunez et al, 2001;Chacur et al, 2003Chacur et al, , 2004Zhang et al, 2017). Interestingly, the presence of a strong catalytic activity in the PLA2s is not essential for its nociceptive activity as observed by the nociceptive effects of PLA2s "Lys49" variants (Lomonte et al, 1994;Rong et al, 2016;Zhang et al, 2017).…”
Section: Phospholipases (Pla2s)mentioning
confidence: 98%
See 3 more Smart Citations
“…This suggests that PLA2s contribute to an increase in arachidonic acid release from cell membranes and its availability to be processed by cyclooxygenase resulting in prostaglandin production (Verri et al, 2006). Corroborating this hypothesis, studies performed in rodents have demonstrated that PLA2s isolated from different snake venoms induced hyperalgesia mediated by biogenic amines, cytokines, prostaglandins, sympathomimetic amines, ATP, K + release, purinergic receptor activation, and glial cell activation (Nunez et al, 2001;Chacur et al, 2003Chacur et al, , 2004Zhang et al, 2017). Interestingly, the presence of a strong catalytic activity in the PLA2s is not essential for its nociceptive activity as observed by the nociceptive effects of PLA2s "Lys49" variants (Lomonte et al, 1994;Rong et al, 2016;Zhang et al, 2017).…”
Section: Phospholipases (Pla2s)mentioning
confidence: 98%
“…A number of PLA2s exert strong myotoxic effects which often lead to severe necrosis (Harris and Maltin, 1982;Gutierrez and Ownby, 2003), and many of these toxins also promote inflammation, including edema formation, cytokine production and leukocyte recruitment, pain by inducing thermal allodynia and mechanical hyperalgesia, paralysis through block of neuromuscular transmission and intensify hemorrhage by inhibiting coagulation (Table 1) (Camara et al, 2003;Chacur et al, 2003;Camargo et al, 2008;Teixeira et al, 2011;Lomonte and Rangel, 2012;Harris and Scott-Davey, 2013;Casais-E-Silva et al, 2016;Costa et al, 2017;Zambelli et al, 2017b;Zhang et al, 2017). Neurotoxic effects caused by these toxins, as well as some of their proinflammatory effects, occurs via the modulation of pre-synaptic terminals as well as sensory nerveendings (Camara et al, 2003;Harris and Scott-Davey, 2013;Sribar et al, 2014;Zhang et al, 2017). The PLA2s pre-synaptic effects are characteristic of β-neurotoxins and target the motor nerve terminals at the neuromuscular junction (Sribar et al, 2014;Gutierrez et al, 2017).…”
Section: Phospholipases (Pla2s)mentioning
confidence: 99%
See 2 more Smart Citations
“…Sequence diversity across taxa is minimal and no new activities have been reported for venom hyaluronidases 37 . In contrast, venom PLA 2 s are more diverse and they have acquired a range of new functions, some of which are independent of their catalytic activity 39,40 . There are only a few reports of lipases in animal venoms, but the H. infensa venom lipase has significant homology to those found to be active in wasp venoms 41,42 .…”
Section: Transcriptomics Uncovers the Biochemical Diversity Of The Hmentioning
confidence: 99%